The Finite Element Method Set - Zienkiewicz, O. C; Taylor, R. L (Elsevier Science & Technology, 2005)
The sixth editions of these seminal books deliver the most up to date and comprehensive reference yet on the finite element method for all engineers and mathematicians.Renowned for their scope, range and authority, the new editions have been significantly developed in terms of both contents and scope.